Menstrual Blood–Derived Mesenchymal Stem Cells Encapsulated in Autologous Platelet-Rich Gel Facilitate Rotator Cuff Healing in a Rabbit Model of Chronic Tears. Issue 7 (June 2023) - Song, Ya; Li, Ping; Xu, Yan; Lin, Zhangyuan; Deng, Zhenhan; Chen, Can
Background: Successful management of chronic rotator cuff (RC) tears remains a challenge owing to its limited intrinsic healing capacity and unsatisfactory failure rate. Menstrual blood–derived mesenchymal stem cells (MenSCs) have the potential to differentiate into the chondrogenic or osteogenic lineage. Autologous platelet-rich gel (APG), a gel material derived from platelet-rich plasma (PRP), can be applied as a carrier system for cell delivery and also as a releasing system for endogenous growth factors. Purpose: To investigate the effect of human MenSCs encapsulated in APG (MenSCs@APG) on the healing of chronic RC tears in a rabbit model. Study Design: Controlled laboratory study. Methods: After evaluation of the effect of PRP on MenSC proliferation or differentiation, the stem cells were encapsulated in APG for in vivo injection. Supraspinatus tenotomy from the right greater tuberosity was performed on 45 New Zealand White rabbits. After 6 weeks, these rabbits were randomly allocated to 3 supplemental treatments during supraspinatus repair: saline injection (control [CTL] group), APG injection (APG group), and MenSCs@APG injection (MenSCs@APG group). At week 18, these rabbits were sacrificed to harvest the humerus–supraspinatus tendon complexes for micro–computed tomography (CT), histological evaluation, tensile test, and MenSC tracking. Results: In vitro results showed that APG can stimulate MenSC proliferation and enhance chondrogenic or osteogenic differentiation. In vivo results showed that APG can act as a carrier for delivering MenSCs into the healing site, and also as a stimulator for enhancing the in vivo performance of MenSCs. Micro-CT showed that bone volume/total volume and trabecular thickness of the new bone in the MenSCs@APG group presented significantly larger values than those of the APG or CTL group ( P < .05 for all). Histologically, compared with the CTL or APG group, significantly more mature fibrocartilage regenerated at the healing site in the MenSCs@APG group. A large number of human nuclei–stained cells were observed in the MenSCs@APG group, presenting a similar appearance to fibrochondrocytes or osteocytes. Biomechanically, the MenSCs@APG group showed significantly higher failure load and stiffness than the APG or CTL group ( P < .05 for all). Conclusion: Human MenSCs@APG facilitated RC healing in a rabbit model of chronic tears. Clinical Relevance: Autogenous MenSCs@APG may be a new stem cell–based therapy for augmenting RC healing in the clinic.